Welfare Assessment and Activities of Captive Elephants in Thailand - Bansiddhi, Pakkanut; Brown, Janine L.; Thitaram, Chatchote (Animals (Basel), 2020)
Thailand is the epicenter of elephant tourism and visiting an elephant camp is a popular activity according to the Tourist Authority of Thailand. However, the welfare of these elephants has been questioned by animal activist groups, international tour operators, and the public. Conclusions that the vast majority of captive elephants are abused often are based on anecdotal evidence and not solid science. So, it is difficult to tease apart emotion, opinion, and fact with regard to what practices are good or bad for elephant welfare. The aim of this paper was to: (1) describe the unique status of captive elephants in Thailand and associated regulations, (2) summarize current issues and challenges facing elephant tourism, (3) review studies conducted on welfare of tourist elephants in Thailand, and (4) offer recommendations for how elephants can be properly cared for under captive conditions in tourist camps. We conclude there are many ways to manage these elephants, and that not all tourist activities are bad for welfare. However, it is essential they be managed in a way that meets physical, physiological and psychological needs, and that management decisions are based on objective data.